2016
DOI: 10.3791/53828
|View full text |Cite
|
Sign up to set email alerts
|

Video Imaging and Spatiotemporal Maps to Analyze Gastrointestinal Motility in Mice

Abstract: The enteric nervous system (ENS) plays an important role in regulating gastrointestinal (GI) motility and can function independently of the central nervous system. Changes in ENS function are a major cause of GI symptoms and disease and may contribute to GI symptoms reported in neuropsychiatric disorders including autism. It is well established that isolated colon segments generate spontaneous, rhythmic contractions known as Colonic Migrating Motor Complexes (CMMCs). A procedure to analyze the enteric neural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 38 publications
0
61
0
Order By: Relevance
“…Previously, we showed that the NL3 R451C mutation decreases colonic motility in response to the serotonergic receptor antagonist, tropisetron compared to WT mice [Swaminathan et al, ]. Whether gut function is changed due to altered neural function involving GABA neurotransmission as reported in the brain of these mice [Etherton et al, ; Tabuchi et al, ] is unknown.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Previously, we showed that the NL3 R451C mutation decreases colonic motility in response to the serotonergic receptor antagonist, tropisetron compared to WT mice [Swaminathan et al, ]. Whether gut function is changed due to altered neural function involving GABA neurotransmission as reported in the brain of these mice [Etherton et al, ; Tabuchi et al, ] is unknown.…”
Section: Resultsmentioning
confidence: 98%
“…Whether gut function is changed due to altered neural function involving GABA neurotransmission as reported in the brain of these mice [Etherton et al, 2011;Tabuchi et al, 2007] is unknown. The use of the video-imaging assay to quantify changes in colonic motility is well established for examining ENS function [Balasuriya, Hill-Yardin, Gershon, & Bornstein, 2016;Roberts et al, 2008;Swaminathan et al, 2016]. This approach takes advantage of the fact that when mouse colon is isolated from the CNS and maintained ex vivo, enteric neural activity drives a stereotyped repetitive motor pattern, the CMMC (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations